Lawrence Wesley Swan (1922-1999) : Raja of the Autonomous Native State of Cooch Nahai - Das, Indraneil; Drewes, Robert C. (Centre for Herpetology, Madras Crocodile Bank Trust, 2001)
Educator and explorer of the high Himalayas and herpetologist, Lawrence Wesley Swan (born 1922), passed away on 5 May 1999. Swan described himself as an “ecologist-zoogeographer, anatomist, evolutionary philosopher with entomological, avicultural, botanical, behavioral and molecular biases and an obdurate dreamer”.